Risk Management and Financial Performance of Indonesia Sharia Banks - Delli Maria; Jaka Darmawan; Indra Caniago; M. Sadat Pulungan (Proceeding International Conference on Information Technology and Business, 2020)
The purpose of this study was to obtain empirical evidence risk management, including financing risk, operational risk, liquidity risk, market risk, and return risk able to improve the financial performance of Sharia Banks in Indonesia. The sample selection in this study used the purposive sampling technique for Indonesia Sharia Banks in 2017-2019. The results of this study indicated that operational risk and market risk significantly improved the performance of Indonesia Sharia Banks. Meanwhile, financing risk, liquidity risk, and return risk had not significantly improved the financial performance of sharia banks in Indonesia.Keywords : Risk Management, Financial Performance, Sharia Banks